A Mixed Methods Genre Analysis of the Discussion Section of MMR Articles in Applied Linguistics. (April 2019) - Hashemi, Mohammad R.; Gohari Moghaddam, Iman
The research article, among other academic genres, has attracted researchers' attention over the past decades. Although sections such as introduction, method, and results and discussion have been addressed in such studies, the mixed methods research (MMR) discussion genre remains underexplored. Thus, the present study aimed at exploring the generic organizational patterns in applied linguistics MMR articles. A qualitatively driven mixed methods approach was utilized to explore 38 MMR discussions. As a result, there emerged a five-move model for genre macro-organization and rhetorical move structure of the MMR discussions. The study concludes by presenting implications for writing effective MMR discussions.